Transient Heat Transfer Characteristics of Twisted Structure Heated by Exponential Heat Flux - Wang, Li; Liu, Qiusheng (Frontiers in Energy Research, 2021)
This study was conducted to investigate the transient heat transfer characteristics of a twisted structure. The twisted structure was heated according to exponential function ( , where is the initial heat generation rate, W/m3; t is time, s; and τ is the period of heat generation rate). A wide range of τ from 37 ms 14 s was applied for the experimental study. A platinum plate with five pitches (each was 180º twisted with 20 mm in length) was used in the experiment. Helium gas with inlet temperature of 298 K under 500 kPa was used as the coolant. The heat transfer coefficient is found to increase with the decrease of τ, and the transition point was estimated to be at about τ=1s. Which means when the increasing ratio of heat generation rate is large enough , the heat transfer enhancement phenomenon will be observed. The response analysis for transient heat transfer at fluid-solid interface was conducted by applying the concept of penetration depth. It is considered that when the penetration depth is smaller than the thermal boundary thickness, heat transfer from the interface (wall surface) to fluid domain is not fully developed during the disturbance.